2010
DOI: 10.1089/end.2009.0194
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience with Laparoscopic Ureteropelvic Junction Release in the Treatment of Ureteropelvic Junction Obstruction

Abstract: Although pyeloplasty remains the preferred treatment for UPJO, UPJ release can be successful in certain circumstances, particularly when significant scarring, inflammation, or fibrosis appears to be the primary etiology of the obstruction. Further investigation is warranted to help define the specific clinical situations in which UPJ release may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Kawauchi 8). However, many other studies report positive patient outcomes without isthmus separation, indicating that isthmus separation may not be the best surgical option (7,9,10). Our study results support this hypothesis; during the operations, the isthmus did not appear to be the cause of the obstructions, and all cases had successful results without isthmus separation.…”
Section: Discussionsupporting
confidence: 76%
“…Kawauchi 8). However, many other studies report positive patient outcomes without isthmus separation, indicating that isthmus separation may not be the best surgical option (7,9,10). Our study results support this hypothesis; during the operations, the isthmus did not appear to be the cause of the obstructions, and all cases had successful results without isthmus separation.…”
Section: Discussionsupporting
confidence: 76%
“…However, they used different techniques in pyeloplasty repair and all of their patients had long segment stricture with a lot of time releasing the upper ureter and renal pelvis to decide type of repair. In addition, Schuster et al (13) reported a mean operative time of 370 ± 76.9 minutes. The patients in their study showed more fibrosis and scaring at the UPJ site due to the multiple previous procedures, which may explains the long operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 studies included, 9 were case series, [14][15][16][17][18][19][20][21][22] 2 were prospective cohort studies, [23,24] and 1 was a retrospective cohort study. [25] Nine studies were conducted in the United States, [14][15][16][17]19,20,22,24,25] and the remaining 3 studies were conducted in the United Kingdom, [23] Israel, [18] and Jordan. [21] All the studies were published in English.…”
Section: Methodological Characteristics and Quality Of Studiesmentioning
confidence: 99%
“…The Gold Journal 1.861 Wadsworth and McClennan [19] 1983 USA Case series Urologic Radiology / Lacey and Massouh [23] 2000 UK Prospective cohort study Clinical Radiology 2.350 Schuster et al [20] 2010 USA Case series Journal of Endourology 2.942 Dajani et al [21] 1982 Jordan Case series British Journal of Urology 5.588 David and Lavengood [22] 1975 USA Case series…”
Section: Imaging and Site Of Obstructionmentioning
confidence: 99%